Effects of Thermomechanical Stimulation During Intravenous Catheter Insertion in Adults: A Prospective Randomized Study. Issue 5 (September 2018) - Redfern, Roberta E.; Micham, Jennifer; Sievert, Deana; Chen, John T.
Abstract : This was an open-label, randomized clinical trial comparing the effects of thermomechanical stimulation (Buzzy) versus no intervention in 105 adults undergoing intravenous (IV) catheter insertion before elective orthopedic surgical procedures. A visual analog scale was used to measure pain; satisfaction questionnaires were administered after IV catheter insertion. There was no significant difference in the mean pain score between the experimental (n = 49) and control (n = 56) groups (2.52 vs 2.43, P = .86). Subjects who reported higher preprocedure anxiety benefited most from the test intervention. It was determined that the application of cold and vibration is not universally effective for pain prevention during IV catheter insertion or for improvement in patient satisfaction in preoperative care.